Faktor Risiko Kejadian Nefropati Diabetika pada Wanita - Sri Wahyuningsih; Heri Nugroho; Suhartono Suhartono; Suharyo Hadisaputro; Mateus Sakundarno Adi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2019)
Background: Diabetic nephropathy was the most frequent complication in diabetics. The prevalence in women at South East Asia country was higher than men, that different than in Europe, American and African. It's a controversial thing. There was no research about the risk factors for diabetic nephropathy in women in Indonesia.Methods: The purpose of this study was to determine the risk factors for stage 3-5 diabetic nephropathy in women. This research used case-control study design. The cases were women with stage 3-5 diabetic nephropathy. Sampling by consecutive sampling technique by comparing the age of the case. Data were analyzed statistically by univariate, bivariate and multivariate using multiple logistic regression analysis.Results: The results of the analysis showed that the risk factors for stage 3-5 diabetic nephropathy were hyperuricemia (OR:9.6; 95%CI:1.870-45.799), lack of physical activity (OR:9.5; 95%CI:1.693-53,287), blood sugar level ≥126 mg/dl (OR:14.7; 95% CI:1.487-145.846), history of oral contraceptive use (OR:7.3; 95%CI:1.254-42.716) and history of obesity (OR:8.9; 95%CI:1.195-65.766).Conclusion: It is recommended for diabetics people to control uric acid levels, fasting blood glucose, body weight and does enough physical activity. For oral contraceptives users it is recommended to consult with a doctor during consumption.